Examination of University Students' Tendencies to Violence and Holiganism in Sports - GÜL, Ali Nadir; YÜKSEL, Oğuzhan; ÜSTÜN, Ümit Doğan (International Journal of Holistic Health, Sports and Recreation, 2024)
In this study, it was aimed to examine the violence and hooliganism tendencies of university students in sports. In the study, 290 university students who continue their education at Hatay Mustafa Kemal University Physical Education and Sports High School participated. In order to determine the distribution of personal information of the participants participating in the study, the "personal information form" created by the researchers was used. There are 9 questions in the form such as gender, age, and the team they support. In order to get the opinions of the participants on the causes of violence in sports, Reyhan et al. (2020) “Basics of violence in sports” scale was used. In the study, the data were analyzed with the SPSS 26 package program for Windows. First, the internal consistency coefficient was calculated for the data collection tool (α=.809; N=25). The distribution of the data was determined by examining the kurtosis and skewness values. In addition to descriptive statistical methods, one-way analysis of variance test, Pearson correlation analysis and independent sample t-test were used in the study. With the results obtained from the survey data; While significant differences were observed in the parameters of the participants' age, gender and being a member of any fan group, there was no significant difference in the parameters of smoking, alcohol use, licensed sports and the frequency of going to the match. In addition, when the survey results are examined, the highest average score obtained by the participants from the scale of the basics of violence in sports is in the "violence caused by referee decisions" sub-dimensions, "violence caused by the media", "violence caused by fans and cheerleaders" and "violence caused by coaches and soccer coaches" was found to be sequential. As a result, when the Violence and Holiganism Tendencies of University Students in Sports are examined; It was seen that male students got higher scores than females. In addition, it was seen that the participants tended to violence mostly due to referee decisions and media.